Current diagnostic imaging of pheochromocytomas and implications for therapeutic strategy - Čtvrtlík, Filip (Exp Ther Med, 2018)
The topic of pheochromocytomas is becoming increasingly popular as a result of major advances in different medical fields, including laboratory diagnosis, genetics, therapy, and particularly in novel advances in imaging techniques. The present review article discusses current clinical, biochemical, genetic and histopathological aspects of the diagnosis of pheochromocytomas and planning of pre-surgical preparation and subsequent surgical treatment options. The main part of the paper is focused on the role of morphological imaging methods (primarily computed tomography and magnetic resonance imaging) and functional imaging (scintigraphy and positron emission tomography) in the diagnosis and staging of pheochromocytomas.